2015
DOI: 10.1002/art.38933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prescription Nonsteroidal Antiinflammatory Drugs on Symptoms and Disease Progression Among Patients With Knee Osteoarthritis

Abstract: Objective The effect of short and long term non-steroidal anti-inflammatory agents (NSAIDs) use on structural change is equivocal. We estimate the extent to which recent and long-term use of prescription NSAIDs relieve symptoms and delay structural progression among patients with radiographically confirmed osteoarthritis (OA) of the knee. Methods We applied a new-user design among participants with confirmed OA not reporting NSAID use at enrollment in the Osteoarthritis Initiative. Participants were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 34 publications
1
59
0
4
Order By: Relevance
“…Current therapy for OA is based on a sequential hierarchical approach, with non-steroidal anti-inflammatory drugs (NSAIDs) as the leading treatment option [3]. Although they exhibit effective pain reduction, the treatment with NSAIDs is limited by complications such as gastroenteropathy, ease of suppression, limited clinical remission rate, immunity, and secondary tumors [4, 5]. An alternative is natural anti-inflammatory agents derived from plants and herbs, such as olive oil, icariin, and angelica polysaccharides, which have potential to prevent cartilage degeneration in patients with OA [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Current therapy for OA is based on a sequential hierarchical approach, with non-steroidal anti-inflammatory drugs (NSAIDs) as the leading treatment option [3]. Although they exhibit effective pain reduction, the treatment with NSAIDs is limited by complications such as gastroenteropathy, ease of suppression, limited clinical remission rate, immunity, and secondary tumors [4, 5]. An alternative is natural anti-inflammatory agents derived from plants and herbs, such as olive oil, icariin, and angelica polysaccharides, which have potential to prevent cartilage degeneration in patients with OA [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with certain anti-inflammatory agents moderately reducing certain OA symptoms. 15,72 However, more detailed studies over longer time periods will be required to understand the mechanisms through which OAC-NM interactions differ from OAC-AM interactions.…”
Section: Toward Modulating Inflammation: Comparison Of Oac-am and Oac-nmmentioning
confidence: 99%
“…However, many in vitro studies investigating NSAID use showed decreased proteoglycan and collagen production in articular chondrocytes [11, [12, [13, [14]. Clinically there is a concern that NSAID use may increase progression of osteoarthritis (OA) over time [15, [16, [17, [18]. …”
Section: Introductionmentioning
confidence: 99%